Acute effects of water immersion on heart rate variability in participants with heart disease. (16th December 2016) - Dionne, Andrée; Leone, Mario; Goulet, Serge; Andrich, David E.; Pérusse, Louis; Comtois, Alain‐Steve
Summary: Background: Water immersion and aquatic exercise can be an important therapeutic tool in patients suffering from heart disease (HD). However, the effects of water immersion on heart rate variability (HRV) in HD participants remain unknown. Methods: Twenty‐eight volunteers in sinus rhythm within the same age range took part in this study: 18 HD and ten healthy controls (HC). Heart rhythm was collected with a heart rate monitor (sampling rate 1000 Hz) for periods of 10 min at rest in the supine position on land, standing on land (STL) and standing in water (STW) to the xiphoid process. Results: Heart disease participants had the same response as HC participants to the three experimental conditions (no significant between‐group differences in all HRV variables). STW (immersion) caused in both groups to increase HRV when compared to supine and STL. Conclusion: Heart disease participants demonstrate similar beneficial adaptations as HC participants to the effects of immersion, reinforcing the concept that immersion can be a valuable aquatic cardiac rehabilitation tool to acutely increase HRV. Approaches that improve HRV in both healthy and cardiac patients may have a positive impact on the reduction of morbidity and mortality.